Pengaruh Sifat Machiavellian, Pressure, dan Opportunity Terhadap Kecenderungan Kecurangan Akuntansi - Venika Mitha Alfiana; Pahala, Indra; Gurendrawati, Etty (Jurnal Akuntansi, Perpajakan dan Auditing, 2025)
This study aims to analyze the influence of Machiavellian traits, pressure and opportunities on accounting fraud tendencies (case study of civil servants in DKI Jakarta). Purposive sampling is the sampling strategy used in this study's quantitative methodologies. The respondents used were 88 Civil Servant (PNS) respondents in the finance department at the DKI Jakarta Regional Revenue Agency. Data collection used was through distributing Google Form questionnaires. Data were processed using SPSS software and analyzed using multiple linear regression analysis. The research results study are: (1) There is a siginificant influence between Machiavellian traits on the tendency for accounting fraud, namely 0,001<0,05. (2) There is a siginificant influence between pressure on the tendency for accounting fraud, namely 0,000<0,05. (3) There is a siginificant influence between opportunity on the tendency for accounting fraud, namely 0,002<0,05.